PENGARUH PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES TERHADAP KESADARAN METAKOGNISI DAN HASIL BELAJAR IPA BIOLOGI SISWA KELAS VIII SMPN 11 MATARAM - Siti SyifaÃ¢â¬â¢un Nufus; Jamaluddin Jamaluddin; Imam Bachtiar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2017)
Abstrak. Pembelajaran berbasis multiple intelligences merupakan pembelajaran yang dapat mengakomodasi tumbuh dan berkembangnya kecerdasan jamak. Tujuan penelitian ini adalah untuk mengetahui pengaruh pembelajaran berbasis multiple intelligences terhadap kesadaran metakognisi dan hasil belajar IPA Biologi siswa. Jenis penelitian ini adalah eksperimen semu (quasy experiment). Populasi penelitian ini adalah siswa kelas VIII SMPN 11 Mataram tahun ajaran 2015/2016, dan penentuan sampel dilakukan dengan teknik non random sampling sehingga didapatkan kelas VIIIA sebagai kelas eksperimen dan kelas VIIIF sebagai kelas kontrol. Instrumen yang digunakan untuk mengukur pembelajaran berbasis multiple intelligences adalah lembar observasi keterlaksanaan RPP, kesadaran metakognisi diukur dengan rubrik MAI (Metacognitive Awareness Inventory) dan penilaian hasil belajar IPA Biologi menggunakan tes pilihan ganda. Data dianalisis menggunakan uji-t. Hasil penelitian menunjukkan bahwa pembelajaran berbasis multiple intelligences memberikan pengaruh yang lebih baik terhadap kesadaran metakognisi dan hasil belajar siswa kelas VIII SMPN 11 Mataram dibandingkan dengan pembelajaran konvensional.ÃÂ Kata-kata Kunci: Pembelajaran Berbasis Multiple Intelligences, Kesadaran Metakognisi, Hasil Belajar IPA BiologiÃÂ Abstract. Multiple-Intelligences-Based (MIB) instruction is an instruction applied to encourage studentsÃ¢â¬â¢ growth and development of multiple intelligence. This study aims to investigate the effect of MIB instruction theory on metacognition awareness and learning outcome in Biology instruction of students. A quasi experimental design was used. Non random sampling was applied based on the research population that covered the student of SMPN 11 Mataram, which resulted VIIIA as the experimental class and VIIIF as the controlled class. In order to determine the effect of MI-based instruction compared with traditional instruction, observation sheets were utilized to assess lesson plan accomplishment. In order to assess the metacognition awareness of the learners in Biology subject, the Metacognitive Awareness Inventory (MAI) was employed and to assess the Biology learning outcome that consisted of multiple-choice test. A t-test for independent sample was used to compare experimental and control groups post-test results. The results of the study indicated that MIB instruction had a significant effect on metacognition awareness and Biology learning outcome of VIII grade students of SMPN 11 Mataram compared with conventional instruction.Keywords: Multiple-Intelligences-Based instruction, metacognition awareness, Biology learning outcome.